Late Cardiac Tamponade in a Patient Victim of Penetrating Trauma – Case Report - Maia,Adnaldo da Silveira (2020)
Abstract Case Presentation: A case of a 49-year-old patient, male, victim of stab wound, developing belatedly cardiac tamponade and hemodynamic stability was reported. The patient underwent a pericardial window with drainage of pericardial effusion of blackened aspect; however, without visualization of the cardiac lesion, enlargement of the incision by median sternotomy was opted for. A hematoma was spotted at the left ventricle with epicardial lesion and a patch of pericardium was made with 3-0 polypropylene. The patient developed acute pulmonary edema and atrial fibrillation, which improved after the intensive care unit clinical management, with hospital discharge in the 7th postoperative day.